A systematic review and meta-analysis of prospective cohort studies on the association between alcohol intake and risk of fracture. Issue 20 (13th November 2022) - Asoudeh, Farzaneh; Salari-Moghaddam, Asma; Larijani, Bagher; Esmaillzadeh, Ahmad
Abstract: Previous studies on the association between alcohol intake and risk of fracture have reached conflicting findings. The aim of this systematic review and meta-analysis of prospective cohort studies was to summarize earlier studies on the association of alcohol intake with risk of fracture. A systematic search of PubMed, Scopus, and ISI Web of Science was conducted up to November 2020. Prospective cohort studies that had considered alcohol consumption as the exposure variable and fracture as the main outcome or as one of the outcome variables were included in this systematic review. Publications in which odds ratios (ORs), rate or risk ratios (RRs), or hazard ratios (HRs) and 95% confidence intervals (CIs) were reported, were included in the meta-analysis. In total, 40 prospective cohort studies including 5, 084, 303 participants and 170, 916 subjects with fracture were included in this systematic review; of them 38 studies with a total sample size of 5, 053, 117 participants and 169, 560 cases of fracture were included in the meta-analysis. Using a random-effects meta-analysis, we found a significant positive association between alcohol consumption and risk of total fractures (RR: 1.35; 95% CI: 1.01, 1.81) and any fractures (RR: 1.24; 95% CI: 1.11, 1.38). However, no significant association was observed between alcohol intake and risk of hip fractures (RR: 1.19; 95% CI: 0.96, 1.48), osteoporotic fractures (RR: 2.01; 95% CI: 0.76, 5.34), vertebral fractures (RR: 0.98; 95% CI: 0.68, 1.40), and wrist fractures (RR: 0.99; 95% CI: 0.85, 1.16). In conclusion, we found that alcohol consumption was positively associated with risk of total fractures and any fractures. However, we did not observe any significant association between alcohol consumption and risk of hip, osteoporotic, vertebral, and wrist fractures.